Síndrome de Evans asociado a infección por citomegalovirus en lactante menor. Reporte de caso - Fátima Rico; Milca Siloé Valladares Valeriano (Revista Médica Hondureña, 2025)
Introduction: Evans syndrome (ES) is characterized by the decrease of two cell lines, primarily red blood cells and platelets. The highest incidence occurs in children between one and four years old, of whom 90% will be asymptomatic. The causes can be of primary etiology or secondary to other diseases, mainly infectious, systemic, autoimmune disorders or primary immunodeficiencies. The etiology can only be determined in 10% of cases, with cytomegalovirus (CMV) being the main infectious agent in infants aged one to six months. Case Description: A case is presented of an infant under 4 months old, previously healthy, who was admitted to the emergency department of the Hospital Escuela due to generalized petechiae and ecchymosis. Bilateral strabismus with vitreous hemorrhage, cerebral calcifications, and splenomegaly were observed. Laboratory tests revealed hemolytic anemia and thrombocytopenia, with these being the only two affected cell lines. Complementary tests showed indeterminate CMV serology and extravascular hemolysis mechanisms. Conclusion: The diagnosis of ES secondary to CMV infection was confirmed through a combination of clinical findings—hemolytic anemia and thrombocytopenia; imaging results—cerebral calcifications on computed tomography (CT) and splenomegaly on ultrasound (USG); and the detection of indeterminate CMV serology. The patient showed improvement after treatment with steroids, immunoglobulin, and antiviral therapy, highlighting the importance of considering various etiologies in the involvement of two cell lines, regardless of age.